2018
DOI: 10.3390/nu10111688
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status, Antidiabetic Properties and Effects on Caco-2 Cells of Colored and Non-Colored Enriched Extracts of Sweet Cherry Fruits

Abstract: This study aimed to compare three different extracts of Saco sweet cherry, namely the non-colored fraction, colored fraction, and total extract concerning phenolic composition, antioxidant and antidiabetic potential, and erythrocytes’ protection and effects on Caco-2 cells. Twenty-two phenolic compounds were identified using high-performance liquid chromatography with diode-array detection. Hydroxycinnamic acids were the most predominant in both the non-colored fraction and total extract, while cyanidin-3-O-ru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
131
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(172 citation statements)
references
References 51 publications
21
131
0
Order By: Relevance
“…Among flavonols, only 3 derivatives were identified: Kaempferol-3-rutinoside, kaempferol-3-glucoside, and quercetin derivative, which were reported previously by Martini, Conte, and Tagliazucchi [5] in exotic varieties and Portuguese varieties, for instance, Saco sweet cherry for Gonçalves, Bento, Silva, and Silva [47], and in Saco cherry polyphenol-rich extracts [8,17]. Regarding anthocyanins, a total of 5 were identified in antioxidant polyphenol-rich extracts: Cyanidin-3-glucoside, cyanidin-3-rutinoside, peonidin-3-rutinoside, peonidin-3-glucoside, and pelargonidin-3-glucoside.…”
Section: Identification Of Major Phenolic Compounds By Lc-esi-qqtof-hrmssupporting
confidence: 75%
See 3 more Smart Citations
“…Among flavonols, only 3 derivatives were identified: Kaempferol-3-rutinoside, kaempferol-3-glucoside, and quercetin derivative, which were reported previously by Martini, Conte, and Tagliazucchi [5] in exotic varieties and Portuguese varieties, for instance, Saco sweet cherry for Gonçalves, Bento, Silva, and Silva [47], and in Saco cherry polyphenol-rich extracts [8,17]. Regarding anthocyanins, a total of 5 were identified in antioxidant polyphenol-rich extracts: Cyanidin-3-glucoside, cyanidin-3-rutinoside, peonidin-3-rutinoside, peonidin-3-glucoside, and pelargonidin-3-glucoside.…”
Section: Identification Of Major Phenolic Compounds By Lc-esi-qqtof-hrmssupporting
confidence: 75%
“…Regarding anthocyanins, a total of 5 were identified in antioxidant polyphenol-rich extracts: Cyanidin-3-glucoside, cyanidin-3-rutinoside, peonidin-3-rutinoside, peonidin-3-glucoside, and pelargonidin-3-glucoside. These anthocyanins had been already identified in the Saco variety [47] and in polyphenol-rich extracts produced from Saco cherry [17], being that these anthocyanins are the most reported in cherries, in spite of the variety. All the extraction methodologies showed to be able to recover all phenolic compounds except on MAE extracts, where three of the hydroxycinnamic acids were not detected.…”
Section: Identification Of Major Phenolic Compounds By Lc-esi-qqtof-hrmsmentioning
confidence: 86%
See 2 more Smart Citations
“…Specifically, previous studies have proven the ability of phenolic-rich ingredients (berry extracts, soft-fruits, grape seeds and bitter melon to inhibit the activities of pancreatic α-amylase and intestinal α-glucosidase in the gut lumen [ 51 , 52 ]. Other studies have shown that anthocyanin-rich fractions from blueberry [ 53 ], blackberry [ 54 ], black legumes [ 55 ], black mulberry [ 56 ], bilberry and cranberry [ 57 ], red aril fruits [ 58 ], camelina and ophia seeds [ 59 ], royle fruits [ 60 ], fruits of Chilean berberis species [ 61 ], peach fruit and A. melanocarpa fruit juice extracts [ 62 , 63 ], colored extracts of Saco sweet cherry [ 64 ], and anthocyanin extracts from black bean hull, black currants and black rice [ 65 , 66 ] exhibited higher effectiveness to inhibit α-glucosidase. Therefore, diet-induced treatments from anthocyanin-based extracts, often combined with other polyphenols, may offer a natural alternative to achieve better glycemic control in T2DM.…”
Section: Why Anthocyanins?mentioning
confidence: 99%